2001
DOI: 10.1044/1092-4388(2001/032)
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Discrimination of Speech Sounds in Developmental Dyslexia

Abstract: Experiments previously reported in the literature suggest that people with dyslexia have a deficit in categorical perception. However, it is still unclear whether the deficit is specific to the perception of speech sounds or whether it more generally affects auditory function. In order to investigate the relationship between categorical perception and dyslexia, as well as the nature of this categorization deficit, speech specific or not, the discrimination responses of children who have dyslexia and those of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
188
3
18

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(225 citation statements)
references
References 52 publications
(76 reference statements)
16
188
3
18
Order By: Relevance
“…Several dyslexic children with the "classic" profile of normal oral language, low phonological awareness, and low nonword reading performed normally on speech perception tasks, and some had better than expected discrimination ability (similar results were reported by Serniclaes et al, 2001), suggesting that their difficulty lies in categorization rather than in more general auditory processing. Thus, it is unlikely that general and extreme problems with speech perception are the cause of any representational problems that children with dyslexia may experience.…”
Section: Introductionsupporting
confidence: 59%
“…Several dyslexic children with the "classic" profile of normal oral language, low phonological awareness, and low nonword reading performed normally on speech perception tasks, and some had better than expected discrimination ability (similar results were reported by Serniclaes et al, 2001), suggesting that their difficulty lies in categorization rather than in more general auditory processing. Thus, it is unlikely that general and extreme problems with speech perception are the cause of any representational problems that children with dyslexia may experience.…”
Section: Introductionsupporting
confidence: 59%
“…Further, using functional magnetic resonance imaging (fMRI), Steinbrink et al (2012) observed decreased activation of left inferior frontal gyrus and insular cortices in dyslexics during processing of the same temporal stimuli, but only in the subgroup of low performing dyslexics (Steinbrink et al, 2012). Also, it should be kept in mind that in certain conditions dyslexics can be even more sensitive to speech sound contrasts, i.e., dyslexics have been reported to be poorer in discriminating between phoneme categories, but more sensitive in discriminating within category contrasts (Serniclaes et al, 2001(Serniclaes et al, , 2004.…”
Section: Speech Perception Related Brain Responsesmentioning
confidence: 99%
“…The stimuli were four sinewave analogues of a CV syllable, used in a previous behavioral study (Serniclaes et al, 2001). The vowel was /a/ and the consonant was varied along a place of articulation continuum, generated by an amplitude-weighted sum of sinusoids.…”
Section: Stimulimentioning
confidence: 99%
“…The end frequencies of SIN2 and SIN3 transitions were fixed at 1300 and 2500 Hz, respectively. The stimuli are labeled according to their phonemic identity for French speakers (i.e., depending on whether they were predominantly identified as /ba/ or /da/ in Serniclaes et al, 2001) and to the onset frequency of SIN2: ba975, ba1250, da1525, da1800. The initial frequency of the lowest frequency component (SIN1, the sinewave equivalent of F1) was 100 Hz and its end frequency was 750 Hz.…”
Section: Stimulimentioning
confidence: 99%